2006
DOI: 10.1002/jcb.21064
|View full text |Cite
|
Sign up to set email alerts
|

Iron chelation study in a normal human hepatocyte cell line suggests that tumor necrosis factor receptor‐associated protein 1 (TRAP1) regulates production of reactive oxygen species

Abstract: Iron is an essential component of many proteins, and has crucial roles in the proper functioning of proteins involved in cellular respiration, proliferation, and differentiation. It has been recently reported that the deferoxamine (DFO), an iron chelator, induces mitochondrial dysfunction, characterized by an attenuation of oxidative phosphorylation, as well as senescence-like cellular morphology. However, the effects of DFO on mitochondrial heat shock proteins (HSPs) remain poorly understood. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
47
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 46 publications
(55 reference statements)
5
47
0
Order By: Relevance
“…overexpression were reported in hepatocytes and PC12 cells (Im et al, 2007;Liu et al, 2005), this is the first evidence, to the best of our knowledge, showing protection against loss of mitochondrial membrane potential and cellular ATP depletion by Hsp75 overexpression. Oxidative stress, mitochondrial dysfunction, and ATP depletion are interconnected during ischemia.…”
Section: Discussionmentioning
confidence: 78%
“…overexpression were reported in hepatocytes and PC12 cells (Im et al, 2007;Liu et al, 2005), this is the first evidence, to the best of our knowledge, showing protection against loss of mitochondrial membrane potential and cellular ATP depletion by Hsp75 overexpression. Oxidative stress, mitochondrial dysfunction, and ATP depletion are interconnected during ischemia.…”
Section: Discussionmentioning
confidence: 78%
“…Much literature has demonstrated that TRAP1 plays an important role in inhibiting cell death caused by a reactive oxygen species (ROS) (23,24). Silencing TRAP1 through siRNA increases ROS accumulation, whereas TRAP1 over-expression decreases ROS production (25,26). Granzyme M, a serine protease capable of inducing apoptosis, can cleave TRAP1 to compromise the ATPase activity and abolish its antagonistic functions against ROSs, resulting in ROS accumulation and cell death (25).…”
Section: Trap1 Protects Mitochondria From Oxidative Stressesmentioning
confidence: 99%
“…Several studies have suggested that TRAP1 plays a cytoprotective role by buffering reactive oxygen species (ROS)-mediated oxidative stress (5,6), and others have reported that TRAP1 overexpression attenuates ROS production (7). The antioxidant properties of TRAP1, together with its reported ability to regulate opening of the mitochondrial permeability transition pore (8,9), may contribute to its antiapoptotic activity (4).…”
mentioning
confidence: 99%